My Religion Keeps Me In Long Distance Marriage (LDM) - Dyah Rachman Kuswartanti (International Journal of Research in Community Services, 2023)
In today's modern era, it is not uncommon to find married couples who do not live together and are geographically separated. This kind of marriage is usually called a Long Distance Marriage (LDM) or Commuter Marriage. Many factors are the reasons why undergoing a long-distance marriage such as improving family life in terms of economy, potentially higher income outside the city, maintaining a career, and better opportunities for career advancement. The condition of commuter marriage is not easy to live if we have strong beliefs such as good religiosity in maintaining marital satisfaction. The purpose of this study was to examine the relationship of religiosity to marital satisfaction in wives who run a commuter marriage. The research subjects were 50 wives who were undergoing long-distance marriages. There are 2 questionnaires used, namely: 1) The Centrality of Religiosity Scale (CRS) questionnaire by Stefan Huber and Odilo W. Huber (2012) and developed by Purnomo & Suryadi (2017) with a reliability value of 0.940. 2) The marital satisfaction questionnaire uses the ENRICH marital satisfaction measuring instrument compiled by Fowers & Olson (1993) and developed by Hermaleni (2018) with a reliability value of 0.973. Analysis of research data using the use of Pearson products. Based on the results of the Pearson product moment analysis, the value that has no reference is 0.454 with p = 0.000; p 0.01, which indicates a significant positive between religiosity and marriage satisfaction of wife who has commuter marriage. This means that the higher the value of the wife's religiosity, the higher her marital satisfaction and vice versa, the lower the value of the wife